Enhanced production of hydrocarbons from lignin isolated from sugarcane bagasse using formic acid induced supercritical ethanol liquefaction followed by hydrodeoxygenation. (December 2021) - Prakash, Dhakshinamoorthy Gnana; Gopinath, Kannappan Panchamoorthy; Vinatha, Viswanathan; Shreya, Suresh; Sivaramakrishnan, Ramachandran; Lan Chi, Nguyen Thuy
Abstract: This study involves the production of hydrocarbons from lignin extracted from sugarcane bagasse using Hydrothermal Liquefaction (HTL) followed by Hydrodeoxygenation (HDO). HTL of the lignin was studied under different solvents-methanol, ethanol and isopropanol in the presence of formic acid as an effective H-donor under varying lignin to solvent ratios (L:S = 1:15, 1:30, 1:40 g/mL), reaction temperatures (200 °C - 320 °C), reaction times (15, 30, 45, 60 min) and ZnCl2 catalyst concentrations (30, 40, 50, 60 wt%). A maximum of 86% lignin derived phenolics was obtained when ethanol was used as solvent at 250 °C under L:S = 1:30 at 30 min reaction time with 60 wt% ZnCl2 . The lignin-oil was upgraded by HDO process in the presence of Ni/Al2 O3 catalyst and a maximum hydrocarbon yield of 73.5% was obtained with a HHV value of 48 MJ/kg. The hydrocarbons had excellent properties with a carbon range of C6 –C12 with a purity of 51.2%. Graphical abstract: Image 1 Highlights: Hydrothermal Liquefaction of isolated lignin done using formic acid as H-donor and ZnCl2 catalyst. 86% of phenolics were produced under 1:30 lignin/ethanol ratio at 250 °C. Hydrodeoxygenation of phenolic products done using Ni/Al2 O3 catalyst. Hydrocarbons with Higher Heating Value of 48 MJ/kg and purity of 51.2% were obtained.